2008
DOI: 10.5194/bg-5-311-2008
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of micro-organisms along a transect in the South-East Pacific Ocean (BIOSOPE cruise) using epifluorescence microscopy

Abstract: Abstract. The distribution of selected groups of microorganisms was analyzed along a South-East Pacific Ocean transect sampled during the BIOSOPE cruise in 2004. The transect could be divided into four regions of contrasted trophic status: a High Nutrient Low Chlorophyll (HNLC) region (mesotrophic) near the equator, the South-East Pacific Ocean gyre (hyper-oligotrophic), a transition region between the gyre and the coast of South America (moderately oligotrophic), and the Chile upwelling (eutrophic). The abund… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 55 publications
2
15
0
Order By: Relevance
“…The occurrence of nano-sized Cyanobacteria had not been reported from a previous survey in the eastern region of the SPSG (Masquelier & Vaulot 2008), suggesting that nanocyanobacteria are constantly scarce in this region.…”
Section: Resultsmentioning
confidence: 85%
“…The occurrence of nano-sized Cyanobacteria had not been reported from a previous survey in the eastern region of the SPSG (Masquelier & Vaulot 2008), suggesting that nanocyanobacteria are constantly scarce in this region.…”
Section: Resultsmentioning
confidence: 85%
“…In the clear waters of the gyre centre autotrophic eukaryotes shift to smaller cells (<2 μm) compared to more eutrophic conditions (Masquelier & Vaulot, 2008). Flow cytometry sorting carried out in the most oligotrophic areas of the gyre revealed several novel lineages of photosynthetic picoeukaryotes such as a clade of prasinophytes.…”
Section: South Pacificmentioning
confidence: 98%
“…In functional diversity, the dominant eukaryotic microbes from the surface until the DCM were heterotrophic nano-and pico-eukaryotes (Masquelier & Vaulot, 2008). Between 150-200 m, heterotrophs represented only 20-40% of eukaryotic microbes, but below 250 m, they increased to 100%.…”
Section: Pelagic Biogeochemistry Of the South Pacific Subtropical Gyrmentioning
confidence: 99%
“…Throughout the gyre between 0-50 m depths, heterotrophs were up to 75-80% of all eukaryotic cells when measured directly by epifluorescence microscopy (Masquelier & Vaulot, 2008). In deeper euphotic zone communities, where photosynthetic cells dominated, dot-blot, clone library, and molecular characterization of cells sorted by flow cytometry found that phylogenetic groups that are usually mixotrophic, such as Haptophytes (Prymnesiophytes) or dinoflagellates, or that might contain mixotrophs (such as the Chrysophyceae among photosynthetic Heterokonts/Stramenopiles) were important or dominant among chlorophyll-containing cells (Lepère et al, 2009;Shi et al, 2009Shi et al, , 2011.…”
Section: Pelagic Biogeochemistry Of the South Pacific Subtropical Gyrmentioning
confidence: 99%